Modern Approaches to Ensuring the Competitiveness of Railway Transport in the Context of the European Integration - M. Posokhov, I.; V. Chepizhko, E. (International Journal of Engineering and Technology, 2018)
The article provides a comparative analysis of the place of Ukraine in the international rankings such as GCI, Doing business, IEF, SPI, CPI. The necessity of transformation and socio-economic features and indicators of development of the existing economic model of Ukraine are researched. The main reasons for the low level of management quality of the enterprises are identified and analyzed. The world experience of the structure of elements and implementation of organizational and economic mechanism of managing the competitiveness of enterprises of individual countries with the most successful indicators of economic development is researched. The main problems of the railway industry and the necessity of continuous improvement of the enterprise competitiveness management system are determined. The article outlines the main directions of increasing the competitiveness and development of rail transport.Â Â